Analysis of Dynamical Interrelations of Electrocardiogram Parameters - Berskiene, K.; Lukosevicius, A.; Jarusevicius, G.; Jurkonis, V.; Navickas, Z.; Vainoras, A.; Daunoraviciene, A. (Elektronika ir Elektrotechnika, 2009)
Mathematical modeling of human physiology is a tremendously ambitious task. The complexity of the problems often stimulates the use of innovative mathematical techniques that are able to capture accurately processes that occur at multiple scales in time and space. The main purpose was to present the analytical method for the analysis of dynamical interrelations of electrocardiogram parameters, cointegrating numeric time series to matrixes by each cardio-cycle. The dynamical interrelations were compared between healthy persons and persons with acute myocardial infarction, also during coronary angiography. The results indicated that ECG signal parameters dynamical interrelations, calculated for each cardio-cycle bring new clinical information, that is not visible in the initial data. Ill. 7, bibl. 13 (in English; summaries in English, Russian and Lithuanian).